New platform supports integrated drought management in Africa and South Asia - Amarnath, Giriraj; Sikka, Alok (International Water Management Institute, 2024)
Knowledge and outputs from IWMI’s two decades of research into monitoring and managing droughts are now available through a single platform. The new website “IWMI Drought Monitor” shares comprehensive information from IWMI’s work implementing drought-management innovations.